ANALYSIS OF INTEREST IN USING BLU DEPOSIT BASED ON TAM - Pangestu, Nathania Clarissa; Pratiwi , Heny; Yusnita, Amelia (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: Digital banking has brought various innovations in financial services, one of which is Blu Deposito by BCA Digital. However, the adoption rate of digital deposit services is still relatively low compared to digital payment services. This study aims to identify and analyze the factors that influence customers' intentions and actual behavior in using Blu Deposito with reference to the Technology Acceptance Model (TAM). This study aims to analyze the factors that influence customers' intentions and actual behavior in adopting Blu Deposito using the Technology Acceptance Model (TAM) framework. Data was collected through a Google Form questionnaire from 54 customers at one BCA branch and analyzed using SPSS through validity and reliability tests, descriptive analysis, and multiple regression. The results show that Behavioral Intention (BI)is significantly influenced by Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Attitude Toward Using (ATU), with PEOU as the most dominant factor. In addition, BI has a significant effect on Actual System Use (AU), which confirms the relevance of applying the TAM model in the context of digital deposit products. These findings indicate that ease of use plays a greater role than financial benefits in encouraging users to adopt Blu Deposits. This study contributes to the understanding of digital deposit adoption and provides managerial insights to improve the usability and user engagement of digital banking services. Keywords: actual system use; attitude toward using; behavioral intention; perceived ease of use; perceived usefulness; technology acceptance model Abstrak: Perbankan digital telah menghadirkan berbagai inovasi dalam layanan keuangan, salah satunya Blu Deposito oleh BCA Digital. Meskipun demikian, tingkat adopsi terhadap layanan deposito digital masih relatif rendah dibandingkan dengan layanan pembayaran digital. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis faktor-faktor yang memengaruhi niat serta perilaku aktual nasabah dalam menggunakan Blu Deposito dengan mengacu pada kerangka Technology Acceptance Model (TAM). Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi niat dan perilaku aktual nasabah dalam mengadopsi Blu Deposito dengan menggunakan kerangka Technology Acceptance Model (TAM). Data dikumpulkan melalui kuesioner Google Form dari 54 nasabah di satu cabang BCA dan dianalisis menggunakan SPSS melalui uji validitas, reliabilitas, analisis deskriptif, dan regresi berganda. Hasil penelitian menunjukkan bahwa Behavioral Intention (BI) dipengaruhi secara signifikan oleh Perceived Ease of Use (PEOU), Perceived Usefulness (PU), dan Attitude Toward Using (ATU), dengan PEOU sebagai faktor paling dominan. Selain itu, BI berpengaruh signifikan terhadap Actual System Use (AU), yang menegaskan relevansi penerapan model TAM pada konteks produk deposito digital. Temuan ini menunjukkan bahwa kemudahan penggunaan memiliki peran lebih besar dibandingkan manfaat finansial dalam mendorong pengguna untuk mengadopsi Blu Deposito. Penelitian ini berkontribusi terhadap pemahaman adopsi deposito digital serta memberikan wawasan manajerial untuk meningkatkan kegunaan dan keterlibatan pengguna pada layanan perbankan digital. Kata kunci: actual system use; attitude toward using; behavioral intention; perceived ease of use; perceived usefulness; technology acceptance model